Mechanical Thrombectomy for Acute Ischemic Stroke Amid the COVID-19 Outbreak: Decreased Activity, and Increased Care Delays. Issue 7 (July 2020) - Kerleroux, Basile; Fabacher, Thibaut; Bricout, Nicolas; Moïse, Martin; Testud, Benoit; Vingadassalom, Sivadji; Ifergan, Héloïse; Janot, Kévin; Consoli, Arturo; Ben Hassen, Wagih; Shotar, Eimad; Ognard, Julien; et al.
Abstract : Background and Purpose: The efficiency of prehospital care chain response and the adequacy of hospital resources are challenged amid the coronavirus disease 2019 (COVID-19) outbreak, with suspected consequences for patients with ischemic stroke eligible for mechanical thrombectomy (MT). Methods: We conducted a prospective national-level data collection of patients treated with MT, ranging 45 days across epidemic containment measures instatement, and of patients treated during the same calendar period in 2019. The primary end point was the variation of patients receiving MT during the epidemic period. Secondary end points included care delays between onset, imaging, and groin puncture. To analyze the primary end point, we used a Poisson regression model. We then analyzed the correlation between the number of MTs and the number of COVID-19 cases hospitalizations, using the Pearson correlation coefficient (compared with the null value). Results: A total of 1513 patients were included at 32 centers, in all French administrative regions. There was a 21% significant decrease (0.79; [95%CI, 0.76–0.82]; P <0.001) in MT case volumes during the epidemic period, and a significant increase in delays between imaging and groin puncture, overall (mean 144.9±SD 86.8 minutes versus 126.2±70.9; P <0.001 in 2019) and in transferred patients (mean 182.6±SD 82.0 minutes versus 153.25±67; P <0.001). After the instatement of strict epidemic mitigation measures, there was a significant negative correlation between the number of hospitalizations for COVID and the number of MT cases ( R 2 −0.51; P =0.04). Patients treated during the COVID outbreak were less likely to receive intravenous thrombolysis and to have unwitnessed strokes (both P <0.05). Conclusions: Our study showed a significant decrease in patients treated with MTs during the first stages of the COVID epidemic in France and alarming indicators of lengthened care delays. These findings prompt immediate consideration of local and regional stroke networks preparedness in the varying contexts of COVID-19 pandemic evolution. Abstract : Supplemental Digital Content is available in the text.